2015
DOI: 10.1002/gcc.22286
|View full text |Cite
|
Sign up to set email alerts
|

Tumor suppressor WWOX moderates the mitochondrial respiratory complex

Abstract: Fragile site FRA16D exhibits DNA instability in cancer, resulting in diminished levels of protein from the WWOX gene that spans it. WWOX suppresses tumor growth by an undefined mechanism. WWOX participates in pathways involving aerobic metabolism and reactive oxygen species. WWOX comprises two WW domains as well as a short-chain dehydrogenase/reductase enzyme. Herein is described an in vivo genetic analysis in Drosophila melanogaster to identify functional interactions between WWOX and metabolic pathways. Alte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 76 publications
1
31
0
Order By: Relevance
“…At least to some extent, this occurs through regulation of the subset of ROS that are also responsive to enzymes of the superoxide dismutase (SOD) family and we have previously shown alterations in isoforms of SOD1 in WWOX mutant flies as well as genetic interactions between WWOX and SOD1 [ 30 ]. However the role for WWOX in the regulation of ROS levels may occur in a context dependent manner given the opposing effects reported for altered ROS in response to modified WWOX expression [ 61 62 ]. In addition, alterations to ROS levels would occur as a consequence of cancer cells shifting their metabolism from oxidative phosphorylation to a more glycolytic Warburg-based metabolism and we have previously shown that WWOX is both responsive to, and contributes to aerobic metabolism [ 30 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At least to some extent, this occurs through regulation of the subset of ROS that are also responsive to enzymes of the superoxide dismutase (SOD) family and we have previously shown alterations in isoforms of SOD1 in WWOX mutant flies as well as genetic interactions between WWOX and SOD1 [ 30 ]. However the role for WWOX in the regulation of ROS levels may occur in a context dependent manner given the opposing effects reported for altered ROS in response to modified WWOX expression [ 61 62 ]. In addition, alterations to ROS levels would occur as a consequence of cancer cells shifting their metabolism from oxidative phosphorylation to a more glycolytic Warburg-based metabolism and we have previously shown that WWOX is both responsive to, and contributes to aerobic metabolism [ 30 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ectopic Eiger/TNFα expression stock ( UAS-egr +w ) was kindly provided by Professor Miura [ 46 ]. WWOX 1 , WWOX 2 , UAS-WWOX ORF #1 and UAS-WWOX cDNA #1 have previously been described [ 49 and 61 ]. MARCMIII and FRT82B , Scrib 1 stocks were kindly provided by Helena Richardson.…”
Section: Methodsmentioning
confidence: 99%
“…We have previously reported the presence of WWOX and p53 in the mitochondria (22,39,44). In addition, WWOX is involved in mitochondrial respiration and metabolism (45,46). By co-immunoprecipitation, yeast two-hybrid analysis, timelapse FRET microscopy, and expression of cloned plasmid vectors, we deciphered how the component proteins in the complex interact with each other and how the action contributes to MOLT-4 maturation.…”
Section: Discussionmentioning
confidence: 99%
“…However, transiently overexpressed WWOX induces mitochondrial apoptosis in vitro [21] , [22] . Transgenic mutant WWOX proteins cause mitochondrial dysfunction by affecting the respiratory complex in Drosophila [23] .…”
Section: Introductionmentioning
confidence: 99%